2020
DOI: 10.47391/jpma.568
|View full text |Cite
|
Sign up to set email alerts
|

Case-control study for assessment of factors associated with periodontitis among adults attending university hospital in Karachi, Pakistan

Abstract: Abstract Objective: To compare the physiological and biochemical markers in healthy and periodontitis subjects, and to relate these markers with the periodontal health condition. Methods: The case-control study was conducted at the Dow University of Health Sciences, Karachi, from April 2017 to March 2018, and comprised systematically healthy controls and periodontitis cases. Periodontal probing depth, clinical attachment loss, oral hygiene indices, educational status and body mass index were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…(18) High risk of Periodontitis is also associated with low socioeconomic status in current study and in Herrera et al, (2018). ( 27) Finding of a case and control study reported by Rafique et al, (2020) in Karachi shows that low education status is associated with Periodontitis that is similar to finding of the current study. (28) In the current study bone loss was measured in OPG x-ray while standard radiograph is periapical, and bitewing for measurement of bone loss however findings of bone loss can be comparable to bitewing.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…(18) High risk of Periodontitis is also associated with low socioeconomic status in current study and in Herrera et al, (2018). ( 27) Finding of a case and control study reported by Rafique et al, (2020) in Karachi shows that low education status is associated with Periodontitis that is similar to finding of the current study. (28) In the current study bone loss was measured in OPG x-ray while standard radiograph is periapical, and bitewing for measurement of bone loss however findings of bone loss can be comparable to bitewing.…”
Section: Discussionsupporting
confidence: 88%
“…( 27) Finding of a case and control study reported by Rafique et al, (2020) in Karachi shows that low education status is associated with Periodontitis that is similar to finding of the current study. (28) In the current study bone loss was measured in OPG x-ray while standard radiograph is periapical, and bitewing for measurement of bone loss however findings of bone loss can be comparable to bitewing. (29) Recently a scientific report was published by Krois et al, (2019) to measure bone loss by deep convolutional neural networks (CNNs) to detect periodontal bone loss (PBL) on panoramic dental radiographs.…”
Section: Discussionsupporting
confidence: 87%